Perancangan Ulang Alat Pembuat Keramik dengan Sistem Penggerak Pedal Searah Berdasarkan Pendekatan Anthropometri sebagai Usaha Pengurangan Beban Kerja - Oktiana Faridatul Khasanah; Irwan Iftadi; Rahmaniyah Dwi Astuti (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2009)
The aim of this paper is redesign the ceramic’s appliance using activator in unidirectional movement base on anthropometri approach as a effort to decrease the work load. The object of this research are workers in Pagerjurang Ceramic Center of Bayat village, Klaten. The redesign steps consist of four steps, this are evaluating the old appliance; determining the new appliance’s specification; technique calculation; and cost calculation. The redesign result is an ceramic’s appliance which the dimension is 73 cm for the high, 60 cm for the wide, and 106 cm for the length. In the length dimension, there are space for the clay material at the left side and space for the ceramics at the right side of the worker. The new appliance activator consist of pedal (kick wheel with manually) and the main energy transmission system using kriwil chain. Pedal related to the chain and spiral spring so that enable the unidirectional foot movement. From the physiology of work show that there is reducing work load when the sample workers tried the new ceramic’s appliance.